We start with the following equality, which we assume to be true:

a + b = c

We can write equality as follows:

(8a-7a) + (8b-7b) = (8c-7c)

Putting all multiples of 7 on one side and 8 on the other, we have:

8a + 8b-8c = 7a + 7b-7c

Highlighting 7 on one side and 8 on the other, we have:

8 (a + b-c) = 7 (a + b-c)

Dividing both sides by a + b-c we have:

**8 = 7**

Obviously this demonstration has an error because we all know that 8 is not equal to 7 (or does anyone have any questions?). Click below to find out what the error is:

In this demonstration comes a stage where we have:

**8 (a + b-c) = 7 (a + b-c)**

According to the demonstration, the next step is to divide both sides by a + b-c.

**There is the mistake !!!**

It is wrong because at first we assume that a + b = c, so a + b-c is worth zero. Division by zero does not exist !!!

Next: Negative Sum